ELECTRONIC DEVICE AND PYROELECTRIC SENSOR - IKEDA, Shinji; SAKURAI, Kazuho (2016)
The purpose of the present invention is, in an electronic device that becomes operational by detecting movement of a subject using a pyroelectric element, to accurately detect subjects by reducing missed detections. The electronic device is provided with a pyroelectric element that detects changes in heat, a detection unit, and a control unit. The detection unit detects movement of a subject on the basis of a detection signal output from the pyroelectric element. The control unit sets the detection sensitivity of the detection unit on the basis of the detection result of the detection unit. The detection sensitivity is set to low sensitivity or high sensitivity. The control unit sets the detection sensitivity to high sensitivity when the detection unit has detected movement of a subject. In the state of the detection sensitivity being high sensitivity, the control unit sets the detection sensitivity to low sensitivity when a predetermined time has elapsed without the detection unit detecting movement of a subject. La présente invention a pour objet, dans un dispositif électronique qui devient opérationnel par détection du mouvement d'un sujet à l'aide d'un élément pyroélectrique, de détecter avec précision des sujets en réduisant les détections manquées. Le dispositif électronique est pourvu d'un élément pyroélectrique qui détecte des changements de chaleur, d'une unité de détection et d'une unité de commande. L'unité de détection détecte un mouvement d'un sujet sur la base d'un signal de détection transmis par l'élément pyroélectrique. L'unité de commande règle la sensibilité de détection de l'unité de détection sur la base du résultat de détection de l'unité de détection. La sensibilité de détection est réglée à une faible sensibilité ou à une sensibilité élevée. L'unité de commande règle la sensibilité de détection à une sensibilité élevée lorsque l'unité de détection a détecté un mouvement d'un sujet. Lorsque l'état de la sensibilité de détection se trouve à une sensibilité élevée, l'unité de commande règle la sensibilité de détection à une faible sensibilité lorsqu'un temps prédéterminé s'est écoulé sans que l'unité de détection ne détecte un mouvement d'un sujet. 焦電素子を用いて被写体の動きを検出して動作する電子機器において、被写体を、検出漏れを低減して精度良く検出する。電子機器は、熱の変化を感知する焦電素子と、検出部と、制御部と、を備える。検出部は、焦電素子から出力される検出信号に基づき、被写体の動きを検出する。制御部は、検出部の検出結果に基づいて、検出部の検出感度を設定する。検出感度は、低感度または高感度に設定される。制御部は、検出部が被写体の動きを検出したとき、検出感度を高感度に設定する。制御部は、検出感度が高感度の状態において、検出部が被写体の動きを検出せずに所定期間が経過したとき、検出感度を低感度に設定する。